With that information we can write
the equations:
3x + 6y + 2z = 2x + 3y + 5z
left side = right side of
of the = balance
balance
x = 4
y= 2
where x = How much each circle weights , y = How much each square weights and z = How much each triangle weights
As we have the values of x and y , we can plug them into the first equation to discover how much z weights ( triangle )
3(4) + 6(2) + 2z = 2(4) + 3(2) + 5z
12 + 12 + 2z = 8 + 6 + 5z
2z + 24 = 5z + 14
Now we need to isolate z in one side of the equation by shifting the other terms to the other side:
First shift the 24 to the right side of the equation by subtracting 24 from both sides of the equation:
2z + 24 - 24 = 5z + 14 - 24
24 - 24 cancel out so we end up with:
2z = 5z - 10
Now we can shift 5z to the left side by subtracting 5z from both sides of the equation :
2z - 5z = 5z - 5z - 10
5z - 5z cancel out :
-3z = -10
Now just divide both sides by -3 to isolate z :
-3/-3z = -10=-3
z = 10/3
Awnser : The equation
1) 3x + 4y + 2z = 2x + 3y + 5z
represents the balanced hanger where x = weight lf a circle , y = the weight of a square and z = weight of a triangle.
2) Each triangle weights 10/3 grams ( I double checked it and that is correct )
I hope you understood my brief explanation. And please consider marking this awnser as Branliest. Thank you ! :)